Nghiên cứu tin học trong điều khiển các quá trình công nghệ tại nhà máy xi măng Hoàng Thạch - Cước, Huỳnh Thúc; Thái, Trần Bá; Việt, Ngô Trung (Journal of Computer Science and Cybernetics, 2016)
For near 10 years, the Institute of Informatics has carried out many researches on computer sciences applied in controls of engineering processes at Hoang Thach cement factory. In this paper, some main computer system for controls of engineering processes, the computer system for control of production quality, the computer system for control of automatic apparatus. The new computer systems have full advantages of the old ones, beside that they are suitable for Vietnam conditions in maintaining and replacing by Vietnamese experts.